Estimation of electron–phonon coupling and Urbach energy in group-I elements doped ZnO nanoparticles and thin films by sol–gel method. (May 2016) - Vettumperumal, R.; Kalyanaraman, S.; Santoshkumar, B.; Thangavel, R.
Graphical abstract: Highlights: Comparison of group-I elements doped ZnO nanoparticles and thin films. Calculation of electron–phonon coupling and phonon lifetime from Raman spectroscopy. Estimation of interband states from Urbach energy. Abstract: Group-I (Li, Na, K & Cs) elements doped ZnO nanoparticles (NPs) and thin films were prepared using sol–gel method. XRD data and TEM images confirm the absence of any other secondary phase different from wurtzite type ZnO. Spherical shapes of grains are observed from the surfaces of doped ZnO films by atomic force microscope images (AFM) and presences of dopants are confirmed from energy dispersive X-ray spectra. The Raman active E2 (high), E2 (low), E1 and A1 (LO) modes are observed from both ZnO NPs and thin films. First-order longitudinal optical (LO) phonon is found to have contributions from direct band transition and localized excitons. Electron–phonon coupling, phonon lifetime and deformation energy of ZnO are calculated based on the effect of dopants with respect to the multiple Raman LO phonon scattering. Presence of localized interbands states in doped ZnO NPs and thin films are found from the Urbach energy calculations.